Exploratory Study of Colloidal Properties of Black Soldier Fly (Hermetia illucens) Larvae Proteins Optimized by Sustainable Approches - Queiroz, Lucas Sales (2022)
The black soldier fly larvae (BSFL), Hermetia illucens (Linnaeus), has been largely utilized for animal feed. Due to its interesting composition, BSFL has shown great potential to be further implemented in the human diet. Herein the main colloidal properties of BSFL protein extract were investigated, gelling, foaming and emulsifying ability were deeply studied. To improve knowledge on protein profile SDS-page electrophoresis, surface hydrophobicity, particle size and -potential Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) and other important methodologies were utilized. Interfacial rheology, shear and dilatational, were evaluated to understand the role of BSFLP when used as surfactant in oil-in-water emulsions. In addition, the physical and oxidative stability of fish oil-in-water (O/W) emulsions were investigated using BSFL protein extract as an emulsifier. Alternative treatment such as ohmic-heating and sonication were applied to verify their impact on protein extraction and functionality. Finally, a study evaluating protein hydrolysis on emulsifying property of BSFL was considered. As a result, the best foam stability was reached at 85 °C with 15 min of treatment. About the gelling behavior, 15 min of ultrasound was able to improve gel-like structure and the gel strength. Ultrasound treatment induced modifications on physicochemical and functional properties of BSFL protein. In emulsion systems, ohmic heated samples had the most interesting physical stability, however, the oxidative stability was not improved under the explored parameters. Considering the emulsions stabilized with hydrolysed protein samples (BSFLPH), it was concluded that, limited hydrolysis had the best physical stability considering the TSI value for 2 days. Both BSFLPH and BSFLP demonstrated surfactant properties as they decreased interfacial tension and created a viscoelastic protective film. Keywords: Black soldier fly. Techno-functionality. Protein extract. Sustainability.